Corporate Social Responsibility and Firm Financial Performance: A Literature Review - Nguyen, Tien; Nguyen, Chi Ha Lien (VNU-HCM Press, 2020)
This paper aims to investigate the literature on Corporate Social Responsibility (CSR) to provide a comprehensive overview of whether CSR would make a difference to organisational financial outcomes. The paper also provides a closer focus on CSR research in Vietnam. Through an extensive analysis of 86 most recent empirical studies from 2015 to 2020, we found that the contribution of CSR to firm financial performance has received significant support from the literature. Yet the overall findings are still inconsistent, and the majority of evidence is mainly from developed countries. The current literature on CSR and firm performance highlights some important issues, ranging from theoretical background, CSR measures, methodological issues, the need to consider intervening factors in CSR-firm performance relationship, and the need to extend this literature further in developing and emerging countries. The literature on CSR-firm performance research in Vietnam closely resembles these problems. Research in this country domain is still scarce in both quantity and quality, reflecting in a number of issues including the limited number of international publications, the absence of theory-driven research, and the less rigorous research design. Building on these findings, we recommend future research to (i) adopt the multi-theoretical approach for a more extensive view on whether and how CSR contributes to firm performance; (ii) obtain more rigorous methodological approaches to measure a wide range of CSR dimensions and address the issue of endogeneity in CSR-firm performance causal relationship; (iii) open the Pandora box to explore why and through which channels CSR can improve firm financial performance with the presence of situational factors; and (iv) build the literature with more evidence from different country contexts and from developing and emerging countries.